Complete Resolution of Severe Decompression Sickness in a Diver Following Oxygen Therapy: A Case Report - Dominikus Evano Putra; Eddy Zulfikar; Usamah Usamah (Archives of Anesthesia and Critical Care)
Decompression sickness (DCS) is a rare but serious risk for divers, characterized by the formation of inert gas bubbles in the bloodstream and tissues due to rapid decompression. This case report highlights a 25-year-old male recreational diver who developed type 2 DCS, presenting with neurological and pulmonary symptoms following a dive. Upon admission to the emergency department, the patient presented with severe shortness of breath, accompanied by nausea, dizziness, numbness and tingling sensations throughout the body, and joint and muscle pain. Physical examination revealed signs of respiratory distress, bilateral upper and lower limb spasticity resembling decorticate posturing, notable hypertonia, and generalized paresthesia. Despite the absence of a hyperbaric chamber facility, the patient was successfully treated with 100% normobaric oxygen (via a Jackson-Rees circuit) and adjunctive medications, including intravenous fluids, dexamethasone, fentanyl, and midazolam, resulting in rapid symptom resolution. The patient was discharged without residual symptoms and remained symptom-free at the one-month follow-up. This case underscores the importance of recognizing DCS and demonstrates that 100% normobaric oxygen therapy and corticosteroids can be effective in treating DCS when a hyperbaric chamber is unavailable.